2023
DOI: 10.1302/0301-620x.105b7.bjj-2022-1369
|View full text |Cite
|
Sign up to set email alerts
|

Is a radiological score able to predict resection-grade chondrosarcoma in primary intraosseous lesions of the long bones?

Abstract: AimsThe preoperative grading of chondrosarcomas of bone that accurately predicts surgical management is difficult for surgeons, radiologists, and pathologists. There are often discrepancies in grade between the initial biopsy and the final histology. Recent advances in the use of imaging methods have shown promise in the ability to predict the final grade. The most important clinical distinction is between grade 1 chondrosarcomas, which are amenable to curettage, and resection-grade chondrosarcomas (grade 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In a retrospective review of 113 patients with a primary chondrosarcoma of a long bone, a group from Toronto (Canada) sought to evaluate the use of a Radiological Aggressiveness Score (RAS) to predict the grade of primary chondrosarcomas in long bones and thus guide management using nine radiological parameters from radiographs and MRI scans. 5 The analysis showed that the parameters that most significantly correlated with a higher grade of tumour were complete cortical erosion, periosteal reaction, a soft-tissue component, marrow oedema, and pathological fracture. A RAS of ≥ four parameters was 97.9% sensitive and 90.5% specific in predicting resection-grade chondrosarcoma.…”
Section: Is a Radiological Score Able To Predict Resection-grade Chon...mentioning
confidence: 98%
“…In a retrospective review of 113 patients with a primary chondrosarcoma of a long bone, a group from Toronto (Canada) sought to evaluate the use of a Radiological Aggressiveness Score (RAS) to predict the grade of primary chondrosarcomas in long bones and thus guide management using nine radiological parameters from radiographs and MRI scans. 5 The analysis showed that the parameters that most significantly correlated with a higher grade of tumour were complete cortical erosion, periosteal reaction, a soft-tissue component, marrow oedema, and pathological fracture. A RAS of ≥ four parameters was 97.9% sensitive and 90.5% specific in predicting resection-grade chondrosarcoma.…”
Section: Is a Radiological Score Able To Predict Resection-grade Chon...mentioning
confidence: 98%
“…Assessing the extent of the disease and predicting the treatment likely to meet with success is essential, and so a team from Toronto (Canada) has contributed by investigating the predictive capability of a radiological score for resection-grade chondrosarcoma. 9 The research involved the analysis of radiological imaging, including radiographs and MRI scans, from a cohort of patients with these lesions to evaluate whether a radiological score could reliably and effectively identify high-grade chondrosarcomas that require extensive resection. The team showed a concordance between resection-grade lesions predicted by the radiological score of 96.46%, whereas concordance between the biopsy grade and the final grade was 63.8, and the ability of initial biopsy to differentiate low-grade from resection-grade chondrosarcomas was 82.9%.…”
Section: Radiological Scoring and Resection Grade For Intraosseous Ch...mentioning
confidence: 99%